The divine proverb of streusel : [large type] a novel - Brunsvold, Sara, 1979- (Center Point Large Print, 2024)
"Shaken by her parents' divorce and discouraged by the growing chasm between herself and her serious boyfriend, Nikki Werner seeks solace at her uncle's farm in a small Missouri hamlet. She'll spend the summer there, picking up the pieces of her shattered present so she can plan a better future. But what awaits her at the ancestral farm is a past she barely knows. Among her late grandmother's belongings, Nikki finds an old notebook filled with handwritten German recipes and wise sayings pulled from the book of Proverbs. With each recipe she makes, she invites locals to the family table to hear their stories about the town's history, her ancestors -- and her estranged father. What started as a cathartic way to connect to her heritage soon becomes the means through which she learns how the women before her endured -- with the help of their cooking prowess. Nikki realizes how a delicious streusel with a healthy dollop of faith can serve as a guide to heal wounds of the past."--